Knowledge and the Use of Pain Assessment Among Critical Care and Surgical Nurses in the Management of Pain in Usmanu Danfodiyo University Teaching Hospital, Sokoto - Akhimie, Oyakilome; Khalid, Sani Dalhat; Salihu, Kombo Abdulrahman; Muhammed, Auwalu; Ladan, Muhammad Awwal (Faculty of Nursing, Universitas Hasanuddin, 2023)
Aim: The purpose of the study was to examine the use of pain assessment scale in pain management among nurses in critical care and surgical areas of Usmanu Danfodiyo University Teaching Hospital, Sokoto. Method: This study employed descriptive cross-sectional design. A stratified random sampling technique was used to select 148 nurses across 5 units within the area of study. Descriptive statistics like frequency, mean, standard deviation and percentage were used to describe distribution of data. Descriptive statistics were utilized in data assessing the distribution of data. Pearson‟s rank correlation was used in determining the relationship between knowledge and level of utilization of pain scales in pain management at the p=0.05 level of significance. A total of 148 study participants were involved in this study. Result: More than half of the nurses, 79 (58.5%), were females; 53 (39.3%) of them were in the age category of 34-39 years. The magnitude of good knowledge towards pain management among nurses was 67.4% with a mean score of 16.41 ± 3.902. The magnitude for the level of utilization of pain assessment scale in pain management was 80% with a mean score of 4.30 ± 0.381. There is a positive relationship between knowledge and utilization of pain assessment scale in pain management with r=0.215. Conclusion: Nurses working in critical care and surgical areas of Usmanu Danfodiyo University Teaching Hospital, Sokoto had good knowledge, and utilize pain assessment tool in pain management than those reported in previous studies in southern Nigeria.